Formal Education System in Iraq: Upskilling and Reskilling for Employment and Self-Reliance - Sultana Begum; Basiru Musa (Eurasian Journal of Management & Social Sciences)
The need for upskilling and reskilling has garnered attention due to the global skills gap and the demand for future jobs. It is estimated that, on average, 42% of the skill demand for jobs across all industries will change between 2018 and 2022 according to UNESCO report of 2021. Failure to meet the skill demands of the new workplace could be as high as $11.5 trillion in G20 states over the next year according to Accenture reports. The skill gap problem is so serious that Garnet recently found that 58% of employees need new skills to do their jobs effectively. This study aims to explore the perceptions of Iraqis regarding the effectiveness of the formal education system in providing them with the necessary skills and training to secure a job, perform their duties effectively, and become self-reliant. The study uses data from the seventh wave of the World Values Survey and includes three variables related to the formal education system and skills required. Gender, age, and education level of respondents are considered as moderators, and cross-tabulation, Chi-Square Test, and Fleiss Kappa are used for analysis. The study’s hypothesis is to determine whether a statistically significant relationship exists between the skills variables and the moderators. The results indicate that over 50% of respondents are dissatisfied with the skills provided by the formal education system for securing a job, performing their duties effectively, or becoming self-reliant. However, the Chi-Square Test indicates no statistically significant relationship between the skills variables and the moderators. The Fleiss Kappa test shows a moderate agreement between the samples. It is recommended that policymakers in Iraq should reconsider their policies and improve the formal education system’s ability to provide relevant skills to the population. Organizations working to meet future skill demands should be supported. The study’s contribution to the contemporary perceptions of the people of Iraq on formal education and skill development highlights the need for skill development to meet the demands of the current and future workforce.